2010
DOI: 10.1152/ajprenal.00710.2009
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperglycemia induces rapid, reversible increases in glomerular permeability in nondiabetic rats

Abstract: Axelsson J, Rippe A, Rippe B. Acute hyperglycemia induces rapid, reversible increases in glomerular permeability in nondiabetic rats. Am J Physiol Renal Physiol 298: F1306 -F1312, 2010. First published March 17, 2010 doi:10.1152/ajprenal.00710.2009.-This study was performed to investigate the impact of acute hyperglycemia (HG) on the permeability of the normal glomerular filtration barrier in vivo. In anesthetized Wistar rats (250 -280 g), the left ureter was catheterized for urine collection, while simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
39
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 33 publications
10
39
0
3
Order By: Relevance
“…De facto, we demonstrated that mice with an episode of severe hyperglycemia over 24 h develop a significant increase in urinary albumin excretion. Our observations are backed by the very recent finding that hyperglycemia induced by glucose infusion increases glomerular permeability in nondiabetic rats; the change in glomerular size selectivity was not related to hyperosmolarity and was reversed after the glucose infusion was ceased (14).…”
Section: Discussionsupporting
confidence: 74%
“…De facto, we demonstrated that mice with an episode of severe hyperglycemia over 24 h develop a significant increase in urinary albumin excretion. Our observations are backed by the very recent finding that hyperglycemia induced by glucose infusion increases glomerular permeability in nondiabetic rats; the change in glomerular size selectivity was not related to hyperosmolarity and was reversed after the glucose infusion was ceased (14).…”
Section: Discussionsupporting
confidence: 74%
“…The slight (but significant) GFR changes are in accordance with our previous findings and those by others, showing a slight increase in GFR over time in Sham animals (5,7,9,39). This is probably related to increases in extracellular fluid volume and less blood sampling during the last period of the experiments.…”
supporting
confidence: 92%
“…More than 97% of the filtered molecules are normally subsequently reabsorbed by the proximal tubules [19,20]. However, the GFB is not a static filter, but rather a highly dynamic sieve, which can directly increase its permeability in systemic inflammation [21], after trauma [22], during hyperglycemia [23], or following elevations of circulating ANP (atrial natriuretic peptide) levels [24], or angiotensin II levels [25]. Our data strongly suggest that albumin and other large proteins, such as IgG (mol.…”
Section: Discussionmentioning
confidence: 99%